2022
DOI: 10.1371/journal.pone.0262682
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electric scooter user kinematics after a crash against SUV

Abstract: The article presents the results of the analysis of electric scooter user kinematics after a crash against a vehicle. The share of electric scooters (e-scooters) in urban traffic has been growing in recent years. The number of road accidents involving e-scooters is also increasing. However, the safety situation of electric scooter users is insufficiently researched in terms of kinematics and injury outcomes. The article presents the importance of this problem based on an in-depth literature analysis of e-scoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In this study, the number of patients with kick-scooter related trauma decreased until 2021 with 29 This suggests that, following the nationwide trend, in our hospital there has been a decline in the number of pediatric trauma patients related to child safety accidents. Notably, after 2019, the decrease in trauma patients was more pronounced owing to the impact of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this study, the number of patients with kick-scooter related trauma decreased until 2021 with 29 This suggests that, following the nationwide trend, in our hospital there has been a decline in the number of pediatric trauma patients related to child safety accidents. Notably, after 2019, the decrease in trauma patients was more pronounced owing to the impact of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 60%
“…Ptak et al 29 reported a maximum acceleration of 777 m/s 2 when a human mannequin riding at 25 km/h on an electric scooter collided with a sports utility vehicle driving at 21.6 km/h. If an adult weighing 60 kg experiences an acceleration of 777 m/s 2 , the maximum force generated is approximately 46,620 N. Considering that 1 kgf equals 9.8 N, the maximum force generated in this case is 4757 kgf.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] Ptak et al, also in a scenario study on three-dimensional models on the analysis of standing e-scooter user kinematics after a collision, emphasized that e-scooters can make users vulnerable to traumatic injuries of various severity and also that there are concerns and doubts about the safety of e-scooters. [ 42 ] Besides, Dozza et al, stressed in a their framework study on comparing bicycles and scooters in data-driven field trials for the safe integration of micromobility into the transportation system, that stand-up e-scooters may be more maneuverable and comfortable than bicycles, although the former require longer braking distances. They also suggest that data about kinematics and controls from micromobility vehicles may help safely integrate these new vehicles into urban transport.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental E-scooter crashes are limited to a few videos of accidents with crash test dummies or volunteers. Ptak et al [ 9 ] studied E-scooter crashes against a vehicle using numerical simulations and provided preliminary data on the head impact kinematics. They reported linear head accelerations between 30 g and 80 g during impact with the car.…”
Section: Introductionmentioning
confidence: 99%